Improving Naïve Bayes Accuracy with Particle Swarm Optimization in Sentiment Analysis of Ibu Kota Nusantara (IKN) - Idris, Irma Surya Kumala; Mustofa, Mustofa (Jambura Journal of Electrical and Electronics Engineering, 2025)
The development of Indonesia's new capital city, Ibu Kota Nusantara (IKN), has sparked extensive public discourse on social media, positioning sentiment analysis as a strategic approach to understanding public opinion. This study assesses the performance of the Naïve Bayes algorithm enhanced through Particle Swarm Optimization (PSO) in classifying public sentiment related to the IKN project, using Indonesian-language comments extracted from the social media platform X. The initial Naïve Bayes model achieved an accuracy of 78.3%, while the PSO-optimized model demonstrated an improved accuracy of 79.7% under optimal parameter settings. These findings indicate the potential of PSO to enhance feature selection effectiveness and reduce classification errors, particularly for positive sentiments. Despite the observed improvements, limitations such as reliance on automated sentiment labeling and challenges posed by linguistic context remain. This study contributes an early exploration of optimization-based methods for public opinion classification and highlights the need for further research involving advanced approaches such as deep learning tailored to the Indonesian language.Pembangunan Ibu Kota Nusantara (IKN) menimbulkan diskursus publik yang luas di media sosial, menjadikan analisis sentimen sebagai pendekatan strategis untuk memahami opini masyarakat. Studi ini mengevaluasi kinerja algoritma Naïve Bayes yang ditingkatkan menggunakan pendekatan Particle Swarm Optimization (PSO) dalam tugas pengelompokan sentimen publik terhadap proyek IKN, dengan menggunakan data komentar berbahasa Indonesia dari platform media sosial X. Hasil awal dari model Naïve Bayes standar mencatat akurasi sebesar 78,3%, sedangkan setelah proses optimasi dengan PSO, akurasi meningkat menjadi 79,7% pada pengaturan parameter terbaik. Hasil ini memperlihatkan potensi PSO dalam meningkatkan efektivitas seleksi fitur dan mengurangi kesalahan klasifikasi, terutama pada sentimen positif. Meski pendekatan ini menunjukkan perbaikan, keterbatasan seperti ketergantungan pada pelabelan otomatis dan konteks linguistik masih menjadi tantangan. Studi ini memberikan kontribusi awal dalam pengembangan metode klasifikasi opini publik berbasis optimasi, serta mendorong eksplorasi pendekatan lanjutan seperti deep learning untuk konteks bahasa Indonesia.